Analisis Ideologi Kolonialisme Dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer Kajian Pos Kolonial - Sri Wahyuni Ningsih; Mila Misrohatul Karomah; Erfania Nabila; Mas’odi (Student Research Journal, 2025)
The importance of literary works in reflecting socio-political conditions during the colonial period, especially in the context of cultural resistance in a novel "Bumi Manusia" by a famous Indonesian writer, Pramoedya Ananta Toer. This study adopts a library method with a descriptive-analytical approach. Primary data is obtained from the novel "Bumi Manusia" and is supported by postcolonial theories from figures such as Edward Said, Homi Bhabha, and Gayatri Spivak. The analysis is carried out by identifying characters, conflicts, and narrative structures that reflect the reality of colonialism and the resistance that emerged against it. The results of the study show that this novel clearly reflects the power relationship between the colonizers and the natives, which is seen through the socio-cultural dominance of the colonial and the struggle to find a national identity, which is represented through the characters of Minke and Nyai Ontosoroh. The conclusion of this study shows that the novel "Bumi Manusia" is not just a literary work that reflects colonial conditions, but also plays a role in fighting the dominant narrative of colonialism by raising the perspective of the natives.